FORENSIC CHARACTERISTICS OF MEDICAL CARE ERRORS COMMITTED BY ANESTHESIOLOGISTS-RESUSCITATORS - Sarvar. A.Khakimov (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Every citizen of the Russian Republic of Uzbekistan is guaranteed by the state, as stated in the constitution, the use of qualified medical care. In recent years, great attention has been paid to measures aimed at improving the quality of medical care. In this matter, the commission of forensic medical expertise on the activities of medical personnel has a special place. It should be noted that the analysis of these materials is neglected.